Perilaku Ekonomi dan Kesejahteraan Sosial dalam Pelajaran IPS di Sekolah - Hasibuan, Sari Mahwati (Al-Azkiya: Jurnal Pendidikan MI/SD, 2025)
Economic behavior and social welfare are two important concepts that are interrelated and play a major role in people's lives. In the context of education, especially Social Sciences (IPS) lessons in schools, these two concepts are taught to shape students' understanding and awareness of the socio-economic conditions around them. This study aims to analyze how IPS lessons integrate the concepts of economic behavior and social welfare in their learning process. The method used in this study is library research, by collecting data from various literature, textbooks, and relevant scientific journals. The results of the study show that IPS learning not only introduces basic economic theory, but also encourages students to think critically about social welfare issues. Through this understanding, students are invited to see how government policies, resource distribution, and individual responsibility can affect shared welfare. Thus, IPS lessons play an important role in shaping the character of students who have social awareness, empathy, and the ability to make wise economic decisions. IPS education is the foundation for growing a generation that cares about sustainable development and the welfare of the wider community.